2016
DOI: 10.1002/micr.30067
|View full text |Cite
|
Sign up to set email alerts
|

Free tissue transfer in Ehlers–Danlos Syndrome

Abstract: Ehlers-Danlos syndrome (EDS) is a spectrum of heritable connective tissue disorders leading to abnormal collagen synthesis, and a triad of skin extensibility, joint hypermobility and tissue fragility. 1 Historically, elective surgery has been avoided in EDS due to wound healing and scarring concerns. 2 We have shown successful free tissue transfer in a patient with EDS.A 44-year-old woman presented with classical EDS and BRCA II gene mutation, requesting bilateral risk reducing mastectomies and immediate autol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…We are unaware of any literature about perforator flaps in patients with vascular EDS. In previous case reports, bilateral deep inferior epigastric perforator flaps were used for breast reconstruction in patients with classical EDS, which is a different subtype of EDS 6 . Yan et al reported the utilization of a free flap in a patient with EDS, but information regarding the specific subtype of EDS was not provided 7 .…”
Section: Discussionmentioning
confidence: 99%
“…We are unaware of any literature about perforator flaps in patients with vascular EDS. In previous case reports, bilateral deep inferior epigastric perforator flaps were used for breast reconstruction in patients with classical EDS, which is a different subtype of EDS 6 . Yan et al reported the utilization of a free flap in a patient with EDS, but information regarding the specific subtype of EDS was not provided 7 .…”
Section: Discussionmentioning
confidence: 99%
“…There is only 1 report of the use of free flap in patients with EDS. Creasy et al described an uneventful experience performing bilateral deep inferior epigastric perforators flaps for breast reconstruction in a patient with classic-type EDS . These authors felt that classic EDS was not a contraindication to microsurgical surgery, but recommended that patients with EDSs be considered on a case by case basis.…”
Section: Discussionmentioning
confidence: 99%